Pelatihan Keselamatan Berkendara untuk Meningkatkan Kemampuan Berkendara Sepeda Motor guna Mengurangi Tingkat Kecelakaan pada Mahasiswa Politeknik Pajajaran - De Keizer, Hendriady; Gunardi; Raihan, Fikri (PADMA, 2024)
Road safety is a serious issue that requires attention from all road users. This article discusses the implementation of a road safety training for Politeknik Pajajaran students aimed at improving understanding and skills in safe driving. The activity was conducted at the Safety riding Center of PT. Daya Adicipta Motor using methods of material briefing, simulation, and field practice. A total of 37 students participated in the training, divided into two batches. Evaluation was carried out through pre-test and post-test using the QUIZIZZ application. Results showed a significant improvement in participants' knowledge and skills after attending the training. In conclusion, this training activity effectively enhanced students' understanding of road safety. It is recommended that similar training be conducted regularly for all Politeknik Pajajaran students to reduce the risk of traffic accidents among students.